Case Report: Metreleptin and SGLT2 Inhibitor Combination Therapy Is Effective for Acquired Incomplete Lipodystrophy - Nagayama, Ayako; Ashida, Kenji; Watanabe, Miki; Moritaka, Kanoko; Sonezaki, Aya; Kitajima, Yoichiro; Takahashi, Hirokazu; Yoshinobu, Satoko; Iwata, Shimpei; Yasuda, Junichi; Hasuzawa, Nao; Ozono, Shuichi; et al. (Frontiers in Endocrinology, 2021)
Childhood cancer survivors (CCSs) who have received bone marrow transplantation with systemic chemotherapy and whole-body irradiation often experience impaired glucose tolerance with marked insulin resistance. Incomplete acquired diabetic lipodystrophy should be considered as a late complication of bone marrow transplantation. A 24-year-old Japanese female patient with incomplete acquired lipodystrophy, a CCS of acute lymphocytic leukemia at the age of 3 years, was treated for diabetes mellitus and dyslipidemia at our hospital. Subcutaneous administration of metreleptin improved her insulin resistance and hypertriglyceridemia within a month; however, it failed to maintain adequate plasma glucose levels in the long term. When an oral administration of 10 mg/day empagliflozin was added to the metreleptin supplementation, her HbA1c value (National Glycohemoglobin Standardization Program) improved from 11% to 8% and was maintained for an additional 18 months. This is the first case report of incomplete lipodystrophy that shows efficacy of a combination therapy with metreleptin and a sodium glucose cotransporter 2 (SGLT2) inhibitor for the treatment of diabetes and dyslipidemia. An SGLT2 inhibitor attenuates hyperglycemia through urinary glucose excretion and has been suggested to enhance lipid catabolism in extra-adipose tissues, especially in the liver and skeletal muscles. Furthermore, metreleptin supplementation could support the action of the SGLT2 inhibitor by promoting satiety and lipolysis through the central nervous system. Combination therapy with metreleptin and an SGLT2 inhibitor was suggested to recover the volume of adipose tissue probably due to the improvement of insulin resistance in adipose tissue. This report highlights the pathophysiological mechanism of an SGLT2 inhibitor in the glucose metabolism improvement of non-healthy lean CCSs with insulin resistance. SGLT2 inhibitor administration, along with metreleptin supplementation, could be a good alternative therapy for diabetic lipodystrophy observed in CCSs.